α-Primitive Elements in the Generalized Verma Modules - Khomenko, О. M. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present explicit formulas for α-primitive elements in the generalized Verma module, which generalize the known formulas for primitive elements in the Verma modules.